2020
DOI: 10.1128/mbio.03203-19
|View full text |Cite
|
Sign up to set email alerts
|

Hijacking the Fusion Complex of Human Parainfluenza Virus as an Antiviral Strategy

Abstract: The receptor binding protein of parainfluenza virus, hemagglutinin-neuraminidase (HN), is responsible for actively triggering the viral fusion protein (F) to undergo a conformational change leading to insertion into the target cell and fusion of the virus with the target cell membrane. For proper viral entry to occur, this process must occur when HN is engaged with host cell receptors at the cell surface. It is possible to interfere with this process through premature activation of the F protein, distant from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 86 publications
0
14
0
Order By: Relevance
“…The first task of the unleashed FI is thought to be capture of the host target membrane by insertion of the fusion peptides at the protomer N-termini. Due to its flexibility the FI extension ranged from ~ 21-30 nm (mean ~ 26 nm), its orientation varied over angles ~ ±60° to the membrane normal, and the FPs in consequence swept out a volume ~ 25,000 nm 1 at rate ~ 750 nm 1 µs 23 (Figures 3d,e, 95% of sampled locations).…”
Section: Large Fluctuations Of the Fusion Intermediate Lead To A Large Membrane Capture Volumementioning
confidence: 99%
See 3 more Smart Citations
“…The first task of the unleashed FI is thought to be capture of the host target membrane by insertion of the fusion peptides at the protomer N-termini. Due to its flexibility the FI extension ranged from ~ 21-30 nm (mean ~ 26 nm), its orientation varied over angles ~ ±60° to the membrane normal, and the FPs in consequence swept out a volume ~ 25,000 nm 1 at rate ~ 750 nm 1 µs 23 (Figures 3d,e, 95% of sampled locations).…”
Section: Large Fluctuations Of the Fusion Intermediate Lead To A Large Membrane Capture Volumementioning
confidence: 99%
“…@A 9: = ℎ 2 >? @A ≈ 0.7 nm µs 23 where the factor of 2 reflects the two membranes. Importantly, binding was mediated by the N-terminal helix of the FP, which provided first contact with the membrane during a binding event (Figure 5b and Supplementary Movie 8).…”
Section: Measurement Of Fusion Peptide-membrane Binding Rate Constantmentioning
confidence: 99%
See 2 more Smart Citations
“…[27][28][29] This study began with a previously reported peptide derived from the HRC domain of HPIV3, designated VIQKI ( Figure 1C), which blocks infection by both HPIV3 and respiratory syncytial virus (RSV). [30][31][32] These two viruses are leading causes of fatal lower respiratory infections in young children. [33][34][35] A crystal structure of VIQKI co-assembled with HPIV3-HRN revealed a six-helix bundle assembly similar to the HRC/HRN assembly in the post-fusion conformation of the HPIV3 F protein ( Figure 1B).…”
mentioning
confidence: 99%